PERCEPTIONS OF MALARIA AND THE UTILISATION OF LONG LASTING INSECTICIDE TREATED NETS IN A RURAL NIGER DELTA COMMUNITY IN NIGERIA - Omole VN; Ogboi SJ; Agu PU; Jarikre E; Audu O; Nmadu AG (Ntec Specialist, 2018)
Introduction: Malaria represents a heavy disease burden with high death tolls in sub-Saharan countries, particularly among children less than five years of age and pregnant women. Misconceptions about the disease are reported to still exist in malaria endemic countries. Insecticide-treated nets (ITNs) have since been advocated as effective control measures against malaria, but how well are they utilised? Objectives: To explore and ascertain the perception of malaria and the utilisation of ITNs in a rural community in the swampy areas of Nigeria's Niger Delta region. Method: A cross-sectional, descriptive study was conducted using simple random sampling technique. Data were collected from household heads with the aid of pre-tested, semistructured, interviewer-administered questionnaires and analysed using SPSS version 17.0. Results: A good perception of the cause (86.9%), mode of transmission (92.8) and preventive measures of malaria were demonstrated. Although, the awareness of ITNs was high (75.6%) with health facilities (35.5%) and radios (33.5%) being the major sources of information, the utilisation rate of ITNs was poor (29%). Conclusion: Intensified efforts by government agencies and diverse stakeholders are recommended to increase the availability and access to ITNs, in order to improve their utilisation rate in rural communities, with adequate priority given to groups at higher risk. Such interventions when implemented consistently and comprehensively are likely to contribute to moving the nation further from malaria control and elimination, towards the possibilities of malaria vaccines and ultimate eradication